CULTURAL REVIVALISM OF MANGKUNEGARA VII AND THE ISLAMISM DISCOURSE IN THE EARLY 20th CENTURY - Wardhana, Adi Putra Surya; Pitana, Titis Srimuda; Susanto, Susanto (ULUL ALBAB Jurnal Studi Islam, 2019)
This article aims at studying Javanese cultural revivalism of Mangkunegara VII, its function, and meaning, within the context of the rise of Islamism in the early 20th century. Mangkunegara VII was a Mangkunegaran ruler who actively participated in developing Javanese culture. When he was young, he was an essential figure in Budi Utomo, a movement organization that represented Javanese nationalism which was influenced by the complex relations between language awareness, colonialism, modernism, and Islamism. He was also involved in various Kejawen organizations. Using Michel Foucault's discourse theory, this paper argues that Javanese cultural revivalism is a Javanese nationalist success to overcome the excessive radicalism of Islamic discourse. When Islamism arose with their attacks against the abangan, he carried out counter-narratives through Javanese cultural organizations. As a ruler, he was successful in assuming legitimacy from the Mangkunegaran people as well as to influence the Dutch colonial government, and other Javanese nationalists as well.